SORPTION-PHOTOMETRIC DETERMINATION OF LEAD AND CADMIUM IN INDUSTRIAL FACILITIES - E. Yu. Shachneva; O. A. Polyakov (Вестник Кемеровского государственного университета, 2015)
The paper studies lead and cadmium ions adsorption on the sorbent SV-1-АL received on the basis of calfskin in Astrakhan Region. Influence of various characteristics on the sorption process is studied, isotherms of static sorption of substances from water solutions are provided, changes in enthalpy (Н), isobar-isotermal potential (G)) and entrophy (S) of sorption are calculated. The received experimental resultы can be used for modelling mechanisms of adsorption.